Book Review: Jan Zielonka, ‘Europe as Empire: The Nature of the Enlarged European Union’ - Sorin Denca (Romanian Journal of European Affairs, 2007)
Jan Zielonka, the author of the book, advances a metaphor and a line of reasoning in favour of enlargement. As metaphor, Zielonka’s book proposes a new angle to understand what at first sight seems difficult to comprehend, namely the complexity and diversity of the European Union project. As an argument for enlargement, the book is an attempt to contrast the positive and negative aspects of this process and using the imperial metaphor to normatively justify it as beneficial for both old and new member states. As structure, the book is balanced, neatly separating the discussion about the impact of enlargement on the nature of the EU from the functioning of an enlarged EU in the fields of economy, democracy and external policy.